Celostna obravnava pojava bolečine v zdravstveni negi - Ščavničar, Ema (Obzornik zdravstvene nege, 2004)
The article presents pain as a complex phenomenon with its physical, psychological, social, cultural and spiritual aspect. Pain is individual and subjective experience and is influenced by personal, cultural and biological factors. Pain is tightly connected with neurophysiology of the body and its intensity can be influenced upon by other factors. Pain is a priority in nursing care. Treatment of pain as a subjective experience represents the starting point in evaluation of needs of an individual for nursing care, in the planning of interventions for the achievement of goals, the process itselfand the evaluation of the planned process.
Keywords: Bolečina; Bolečina, merjenje; Bolečinski prag; Negovalna diagnoza; Neuralgia; Nevralgija; Nociceptorji; Nociceptors; Nursing; Nursing Diagnosis; Pain; Pain Measurement; Pain Threshold; Physiopathology; zdravstvena nega